2007
DOI: 10.1128/aem.00537-07
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Visualization of aCoxiella-Type Symbiont within the Lone Star Tick,Amblyomma americanum

Abstract: A Coxiella-type microbe occurs at 100% frequency in all Amblyomma americanum ticks thus far tested. Using laboratory-reared ticks free of other microbes, we identified the Amblyomma-associated Coxiella microbe in several types of tissue and at various stages of the life cycle of A. americanum by 16S rRNA gene sequencing and diagnostic PCR. We visualized Amblyomma-associated Coxiella through the use of a diagnostic fluorescence in situ hybridization (FISH) assay supplemented with PCR-based detection, nucleic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
132
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(150 citation statements)
references
References 56 publications
13
132
1
Order By: Relevance
“…Previous studies have suggested that the Coxiella-like symbiont in A. americanum is a primary symbiont because of its ubiquitous distribution (21,30), vertical transmission (13,21), infection of specific tissues (13), loss of fitness with antibiotic treatment (31), and reduced genome (30). In this study, we found that CLS-Ds exhibited vertical infection and infected specific tissues.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Previous studies have suggested that the Coxiella-like symbiont in A. americanum is a primary symbiont because of its ubiquitous distribution (21,30), vertical transmission (13,21), infection of specific tissues (13), loss of fitness with antibiotic treatment (31), and reduced genome (30). In this study, we found that CLS-Ds exhibited vertical infection and infected specific tissues.…”
supporting
confidence: 54%
“…To date, a wide range of symbionts, such as Coxiella-like (13), Francisella-like (14), Wolbachia-like (15), Rickettsia-like (16), Arsenophonus-like (17), "Candidatus Midichloria mitochondrii" (18), and Rickettsia peacockii (19) symbionts, have been detected in several tick species. However, little attention has been given to coinfection with multiple symbionts of ticks.…”
mentioning
confidence: 99%
“…These pathogens are apparently in the final stages of host cell adaptation and have cleared most pseudogenes from their respective genomes (2). A nonpathogenic progenitor of C. burnetii has not been identified; however, Coxiella-like endosymbionts of ticks are highly prevalent and may represent nonpathogenic ancestors of virulent C. burnetii (57).…”
Section: Vol 77 2009mentioning
confidence: 99%
“…Recently, many Coxiella -like bacteria have been reported in ticks. Ticks infected with Coxiella -like bacteria include Amblyomma americanum Klyachko et al 2007 ;Clay et al 2008 ) , Carios capensis (Reeves et al 2005 ) , Haemaphysalis longicornis (Noda et al 1997 ;Lee et al 2004 ) , Ixodes ricinus (Schabereiter-Gurtner et al 2003 ) , I. woodi (Kurtti et al 2002 ) , Ornithodoros moubata (Noda et al 1997 ) , Rhipicephalus sanguineus (Noda et al 1997 ;Bernasconi et al 2002 ) , and R. turanicus (Bernasconi et al 2002 ) .…”
Section: Introductionmentioning
confidence: 98%